An Aspect of Functional Harmony in Schoenberg's Early Post‐Tonal Music. (11th September 2013) - Newton, Neil
Abstract Two views of Schoenberg's post‐tonal music are common: that it is non‐functional, and that there was a complete break from the tonal music that preceded it. In this article I show that there are aspects of functional voice leading, derived from tonality, that are still present in Schoenberg's early post‐tonal music. Furthermore, this functional harmony also helps to communicate the form of the piece and to supply closure.